Case Report: Resuscitation of patient with tumor-induced acute pulmonary embolism by venoarterial extracorporeal membrane oxygenation - Zhang, Shuang-Long; Zhang, Qi-Feng; Li, Gang; Guo, Miao; Qi, Xiao-Xia; Xing, Xiao-Hui; Wang, Zheng (Frontiers in Cardiovascular Medicine, 2024)
Background Pulmonary embolism is a condition of right cardiac dysfunction due to pulmonary circulation obstruction. Malignant tumor-induced pulmonary embolism, which has a poor therapeutic outcome and a significant impact on hemodynamics, is the cause of sudden death in patients with malignant tumors. Case description A 38-year-old female patient, who had a medical history of right renal hamartoma, and right renal space-occupying lesion, was admitted to the hospital. During the procedure to resect the right renal malignancy, the blood pressure and end-tidal carbon dioxide level dropped, and a potential pulmonary embolism was considered as a possibility. After inferior vena cava embolectomy, the hemodynamics in the patient remained unstable. The successful establishment of venoarterial extracorporeal membrane oxygenation (VA-ECMO) resulted in the stabilization of her hemodynamics and ventilation. On Day 2 of VA-ECMO support, her respiration and hemodynamics were relatively stable, and ECMO assistance was successfully terminated following the “pump-controlled retrograde trial off (PCRTO)” test on Day 6. The patient improved gradually after the procedure and was discharged from the hospital after 22 days. Conclusion VA-ECMO can be used as a transitional resuscitation technique for patients with massive pulmonary embolism. It is critical for the perfusion of vital organs and can assist with surgical or interventional treatment, lower right heart pressure, and hemodynamic stability. VA-ECMO has a significant impact on patient prognosis and can reduce the mortality rate.